In-situ monitoring of fatigue crack growth using high frequency guided waves. (April 2015) - Masserey, B.; Fromme, P.
Abstract: The development of fatigue cracks at fastener holes represents a common maintenance problem for aircraft. High frequency guided ultrasonic waves allow for the monitoring of critical areas without direct access to the defect location. During cyclic loading of tensile, aluminum specimens fatigue crack growth at the side of a fastener hole was monitored. The changes in the energy ratio of the baseline subtracted reflected guided wave signal due to the fatigue damage were monitored from a stand-off distance using standard ultrasonic pulse–echo measurement equipment. Good sensitivity for the detection and monitoring of fatigue crack growth was found. Highlights: High frequency guided ultrasonic wave propagation in aerospace structures. Adequate propagation distance and detection sensitivity for small defects. Standard pulse–echo measurements for monitoring of fatigue cracks at fastener hole. Fatigue crack detection from stand-off distance without access to damage location.